Evaporation Characteristics of a Single Desulfurization Wastewater Droplet in High-temperature Gas. (April 2022) - Zhan, Lingxiao; Shen, Tiejia; Chen, Heng; Gu, Liyan; Zhou, Hao; Feng, Qianyuan; Yang, Linjun; Zhao, Ning; Feng, Yongxin
Highlights: Evaporation characteristics of desulfurization wastewater droplets over 300°C are investigated using in-situ SDD devices. The droplet evaporation process of wastewater is divided into five stages. Evaporation rate and particle morphology are impacted by wastewater composition and drying temperature. Higher ambient temperature initiates a more violent expansion of semi-dried particles. A Modified REA approach can correctly predict evaporation kinetics. Abstract: Understanding the high-temperature evaporation process of atomized wastewater droplets is a prerequisite for designing an efficient spray evaporation wastewater treatment facility. However, some dynamic characteristics during the evaporation of high-temperature wastewater droplets have not yet been fully understood. Here, the convective evaporation process of desulfurization wastewater droplet in high-temperature gas, which is commonly encountered in the spray drying technology to treat desulfurization wastewater in power plants, was investigated adopting the single droplet drying (SDD) device. In-situ droplet information including the morphology, radius, temperature, and mass was recorded. The influence of bulk temperature and the initial concentration of dissolved solids on evaporation kinetics was studied. To explore the development of resistances during the evaporation process as well as develop a reliable and flexible droplet evaporation model useful for CFD simulations, experimental results were correlated with a modified Reaction Engineering Approach (REA) framework, which revised the previous linear shrinkage model into a hybrid model to illustrate the droplet/particle deformation considering the possible inflation phenomenon at elevated temperatures. The results show that crust formation and internal bubble nucleation induced by wastewater components contributed to unique evaporation features including decreasing evaporation rate and inflation of semi-dried particles. Increasing bulk temperature enhanced the evaporation rate and the degree of inflation. Finally, the rapid and accurate prediction of the modified REA model elucidated its effectiveness to illustrate the whole evaporation and drying process.